The acquisition of locative alternation: a multiple account - Chau, Dung Duc; Nguyen, Huong Thi Linh (Penerbit Universiti Kebangsaan Malaysia, 2025)
This article explores how Vietnamese EFL learners acquire locative alternation, focusing on three types of verbs. It aims to identify which locative structures are challenging for these learners and the underlying reasons. The study involved 72 participants, divided into two groups: an experimental group of 36 Vietnamese learners of English and a control group of 36 native English speakers, used as a benchmark for cross-group comparisons. The learners were classified as upper-intermediate based on their Michigan test scores and had to pass a Word-Meaning Matching Task to participate. All stimulus sentences were rated on a five-point Likert scale. The findings suggest that learning locative structures is a complex developmental process influenced by various factors such as overgeneralisation, verb meanings, learners' English proficiency, and narrow-range verb classes. These insights have significant implications for both teaching methods and SLA.